Socio-Cultural Practices and Entrepreneurial Behavior among the Tiv People in Benue State, Nigeria (International Journal of Scientific Research and Management (IJSRM), 2017)
The study examines the Effect of Socio-cultural Practices on Entrepreneurial Behaviour in Benue State with emphasis among the Tiv people. Structured Questionnaire instrument with five likert scale was used for primary data collection, a survey research method was adopted and a sample size of 400 respondents was used. While secondary information were gathered from previous research studies done by different authors in journals, textbooks and internet among others. The data were analyzed using descriptive statistical tools such as tables and simple percentage. Furthermore, multiple regressions were used for further analysis and test of hypotheses. The findings from this study indicate that there was an established relationship between dimensions of socio-cultural practices and entrepreneurial behaviour. The study revealed that most of socio-cultural factors have negative effect on entrepreneurial behaviour in Tivland, and Benue state at large. The study made some recommendations based on the research findings, some of which are; social groups, traditional and religious institutions should roll out policies and sensitization programmes that will help discourage cultural practices that are capable of retarding entrepreneurial behaviour of people in Tivland such as high cost of funeral ceremonies, rather, promote the culture of investing such funds in small businesses. Family members in Tivland should always be involved in training their young ones through family businesses to let them have business background right from their childhood so as to give them initial orientation and encourage them on the need to be independent through generation of business ideas, venture creation, purchases and sales of goods. This will help in boosting entrepreneurial behaviour and entrepreneurship development in Tivland, Nigeria and the world at large.